Relativistic equation-of-motion coupled-cluster method for the electron attachment problem - Pathak, Himadri; Sasmal, Sudip; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Computational and Theoretical Chemistry, 2016)
The article considers the successful implementation of relativistic equation-of-motion coupled cluster method for the electron attachment problem (EA-EOMCC) at the level of single- and double- excitation approximation. The implemented relativistic EA-EOMCC method is employed to calculate ionization potential values of alkali metal atoms (Li, Na, K, Rb, Cs, Fr) and the vertical electron affinity values of LiX (X = H, F, Cl, Br), NaY (Y = H, F, Cl) starting from their closed-shell configuration. Both four component and exact two-component calculations are done for all the opted systems. Further, we have shown the effect of spin-orbit interaction considering the atomic systems. The results of our atomic calculations are compared with the values from the NIST database and the results are found to be very accurate (<1%). (C) 2015 Elsevier B.V. All rights reserved.